Le gouvernement de l'Indonésie par l'islam et la science. Visions d'intellectuels en quête de pouvoir - François Raillon (Revue des Mondes Musulmans et de la Méditerranée)
With general Suharto's takeover in 1966, Muslim intellectuals thought that they had a chance to advance their views of a scientific Islam and to take control of the Indonesian state. Their strategy and efforts to reach this aim, despite Soharto's opposition, are analyzed in this article. In spite of engineer Habibie's becoming president in 1998, their quest for power was thwarted by the economic and political crisis that hit Indonesia. Habibie's successor, A. Wahid, was more supportive of liberal democracy than of political and religious scientism. His undoing by Megawati confirmed the –temporary ? - end of the Muslim modernists' dream in favor of an emerging Indonesian populism.